2013
DOI: 10.19106/jmedscie004501201305
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of platelet refractoriness in children

Abstract: Therapeutic platelet transfusions are often performed in pediatric patients with various indications. However, the platelet transfusion has potentially induced more harm than good for some patients. Therefore, its effectiveness needs to be evaluated. This study aimed to evaluate the clinical risk factors namely sepsis, splenomegaly, DIC (disseminated intravascular coagulation), severe bleeding and the history of platelet transfusion in the incidence of platelet refractoriness. This was a casecontrol study cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…All subjects with sepsis experienced platelet refractory but the bivariate analysis shown no significant difference between sepsis and platelet refractory after platelet concentrate transfusion. This is different from the study of Purba et al which stated that sepsis is an independent risk factor for platelet refractory in children with an OR of 2.96 (Purba et al, 2013). These can occur due to differences in the structure of bacteria that cause sepsis such as lipopolysaccharides and endotoxins that also activate platelets directly (Levi, 2005).…”
Section: Discussionmentioning
confidence: 63%
“…All subjects with sepsis experienced platelet refractory but the bivariate analysis shown no significant difference between sepsis and platelet refractory after platelet concentrate transfusion. This is different from the study of Purba et al which stated that sepsis is an independent risk factor for platelet refractory in children with an OR of 2.96 (Purba et al, 2013). These can occur due to differences in the structure of bacteria that cause sepsis such as lipopolysaccharides and endotoxins that also activate platelets directly (Levi, 2005).…”
Section: Discussionmentioning
confidence: 63%
“…The incidence is assumed to be lower, as children are less likely than adults to have been sensitized to platelets by blood transfusions and pregnancy 25 . Limited studies have been published on pediatric PTR, with the majority published over 10 years ago 14–19 . It is challenging to compare the pediatric PTR results from the current study to those previously reported for a number of reasons.…”
Section: Discussionmentioning
confidence: 87%
“…25 Limited studies have been published on pediatric PTR, with the majority published over 10 years ago. [14][15][16][17][18][19] It is challenging to compare the pediatric PTR results from the current study to those previously reported for a number of reasons. First, different definitions were used for PTR, with some including HLA testing and others not.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations